Individual Responsiveness to Exercise-Induced Fat Loss and Improvement of Metabolic Profile in Young Women is Associated with Polymorphisms of Adrenergic Receptor Genes - Agata Leońska-Duniec, Zbigniew Jastrzębski, Aleksandra Jażdżewska, Waldemar Moska, Ewelina Lulińska-Kuklik, Marek Sawczuk, Svetlana I. Gubaydullina, Alsu T. Shakirova, Pawel Cięszczyk, Adam Maszczyk, Ildus I. Ahmetov (Journal of Sports Science and Medicine, 2018)
The effectiveness of physical exercise on fat loss and improvement of aerobic capacity varies considerably between individuals. A strong linkage exists between common allelic variants of the adrenergic receptor genes and weight gain, as well as changes in body composition. Therefore we aimed to check if body composition and metabolic variables were modulated by the ADRB2 (Gly16Arg and Glu27Gln), ADRB3 (Trp64Arg) and ADRA2A (rs553668 G/A) gene polymorphisms in 163 Polish sedentary women (age 19-24; body mass index (BMI) 21.7 ± 0.2 kg·m-2) involved in a 12-week aerobic training program. Only 74.8% of participants lost fat mass. On average, participants lost 5.8 (10.4)% of their relative fat mass with training (range: +28.3 to -63.6%). The improvement of VO2max was significantly greater in women who could lose their fat mass compared to women who were unsuccessful in fat loss (4.5 (5.6)% vs. 1.5 (3.8)%; p = 0.0045). The carriers of a low number (0-3) of obesity-related risk alleles (ADRB2 Gly16, ADRB2 Glu27, ADRA2A rs553668 G) were more successful in fat mass loss compared to the carriers of a high number (5-6) of risk alleles (7.7 (9.8) vs 4.0 (9.4)%, p = 0.0362). The presented results support the assumption that variation within adrenergic receptor genes contributes to interindividual changes of body composition in response to physical exercise.